Cultivation of S. molesta plants for phytoremediation of secondary treated domestic wastewater - Mustafa H.M.; Hayder G. (Ain Shams University, 2023)
Agricultural robots; Aquatic ecosystems; Bioremediation; Cultivation; Environmental Protection Agency; Eutrophication; Free energy; Hydrogeology; Nitrates; Spectrophotometry; Turbidity; Wastewater treatment; Water pollution; Cyanobacteria blooms; Domestic wastewater; Municipal wastewaters; Natural water bodies; Physico-chemical analysis; Reduction efficiency; Relative growth rate; Spectro-photometric method; Sewage treatment plants